PENGARUH KETERLIBATAN AUDITOR INTERNAL DALAM MANAJEMEN RISIKO PERUSAHAAN - Yosua Hasudungan Nainggolan; Endang Kiswara (Diponegoro Journal of Accounting, 2013)
This study is to examine and give evidence empirical on the influence of level involvement of internal auditor and characteristic relations with auditor internal audit committee against reporting damage procedure risk management company. This research is replication of research de Zwaan, et al( 2009 ) who examines about the role of internal auditor in risk management companies in Australia with test level involvement of internal auditor in risk management and characteristic relations with auditor internal audit committee. On current internal auditors should role well based on procedure and duty anyway because almost any company currently has implemented risk management company ( ERM ).There are 2 variables in this research, namely the levels the involvement of internal auditor with an indicator ERM roles and characteristic of relations with the auditors internal audit committee with an indicator the level of objectivity. The population of this research is the internal auditor and audit committee working state companies. A sample of research accounts for 47 one who will next measured based on high and low level of involvement in the company, they risk management weak and strong their relationships with audit committee. The method used is a 2-way ANOVA method. Based on the results of the study can be obtained from the conclusion that the internal auditor's engagement level high in ERM influential negatively to reporting procedures, the risk of damage while the characteristics of the internal auditor's relationship with the audit committee has no effect on the reporting of the damage risk procedures. The implication of this research is the internal auditor should not be too involved in the risk management process and the level of objectivity that should always be observed, although there is a strong relationship with the audit committee.